2014
DOI: 10.1525/nclr.2014.17.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Comprehension of Jury Instructions in Criminal Trials

Abstract: It would seem important that jury instructions are clear and comprehensible to jurors if they are to effectively carry out their responsibility in criminal trials. Research suggests, however, that jurors may not fully understand instructions despite reporting high levels of comprehension. The current study (N = 33) surveyed jurors who had recently served on a jury to assess their level of comprehension and the factors that contributed to their decisions. It was found that a substantial proportion of jurors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Reifman et al (1992) found that jurors only correctly understood half of the procedural instructions given by the judge about how to evaluate the evidence in the case. Similarly, McKimmie et al (2014) found when asked only one third of jurors accurately described procedural instructions (e.g., the burden of proof and the concept of reasonable doubt) in their own words. Rose and Ogloff (2001) found that participants’ comprehension of judicial instructions about evaluating witness testimony given by a coconspirator was consistently poor.…”
Section: Barriers To Conviction In Rape Trialsmentioning
confidence: 86%
“…Reifman et al (1992) found that jurors only correctly understood half of the procedural instructions given by the judge about how to evaluate the evidence in the case. Similarly, McKimmie et al (2014) found when asked only one third of jurors accurately described procedural instructions (e.g., the burden of proof and the concept of reasonable doubt) in their own words. Rose and Ogloff (2001) found that participants’ comprehension of judicial instructions about evaluating witness testimony given by a coconspirator was consistently poor.…”
Section: Barriers To Conviction In Rape Trialsmentioning
confidence: 86%
“…Much of the literature on lay-comprehension of law and legal concepts focuses specifically on the clarity and comprehensibility of judicial instructions, and how well juries understand and apply those directions when deliberating. 63,64 While an important area for academic consideration, once a case has been handed over to the jury it is too late to begin contemplation as to whether those not trained in law but present in court have understood what occurred. Confusion around legal obligations and rights pervades all aspects of life.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings should be considered in light of recent research on jurors’ assessment of expert evidence. One study found that attending to witness demeanour can override a full consideration of the strength of the witness’ testimony (McKimmie et al, 2014). Another found that jurors who perceived a prosecution expert to be confident were more likely to report that expert’s evidence as easy to understand and to perceive the prosecution case as stronger (Freckelton et al, 2016: para 9.37).…”
Section: Discussionmentioning
confidence: 99%